Development of Nanocomposite Films with Durian Peel Nanocrystalline Cellulose - Zeinur Rochma Fandis Romadhon; I Gusti Made Sanjaya (Universitas Tadulako, 2021)
This research aims to synthesize and characterize nanocomposite film with nanocrystalline cellulose (NCC) durian peel waste filler. Nanocomposite film was prepared by adding NCC with concentrations of 0%, 1%, 3%, 5%, and 7% to each mixture of chitosan and guar gum. Characterization of nanocomposite film includes tensile strength test, elongation test, water-resistance test, and biodegradability. Nanocomposite film with NCC 7% showed a tensile strength value of 21.988 MPa; elongation of 10.3%; and experienced degradability of 4.05 mg/day, besides the characterization of the equal distribution of NCC in the chitosan-guar gum matrix was proven from the SEM results.